Using naso- and oro-intestinal catheters in physiological research for intestinal delivery and sampling in vivo: practical and technical aspects to be considered - van Trijp, Mara PH; Wilms, Ellen; Ríos-Morales, Melany; Masclee, Ad Am; Brummer, Robert Jan; Witteman, Ben JM; Troost, Freddy J; Hooiveld, Guido Jej (The American journal of clinical nutrition, 2021)
Intestinal catheters have been used for decades in human nutrition, physiology, pharmacokinetics, and gut microbiome research, facilitating the delivery of compounds directly into the intestinal lumen or the aspiration of intestinal fluids in human subjects. Such research provides insights about (local) dynamic metabolic and other intestinal luminal processes, but working with catheters might pose challenges to biomedical researchers and clinicians. Here, we provide an overview of practical and technical aspects of applying naso- and oro-intestinal catheters for delivery of compounds and sampling luminal fluids from the jejunum, ileum, and colon in vivo. The recent literature was extensively reviewed, and combined with experiences and insights we gained through our own clinical trials. We included 60 studies that involved a total of 720 healthy subjects and 42 patients. Most of the studies investigated multiple intestinal regions (24 studies), followed by studies investigating only the jejunum (21 studies), ileum (13 studies), or colon (2 studies). The ileum and colon used to be relatively inaccessible regions in vivo. Custom-made state-of-the-art catheters are available with numerous options for the design, such as multiple lumina, side holes, and inflatable balloons for catheter progression or isolation of intestinal segments. These allow for multiple controlled sampling and compound delivery options in different intestinal regions. Intestinal catheters were often used for delivery (23 studies), sampling (10 studies), or both (27 studies). Sampling speed decreased with increasing distance from the sampling syringe to the specific intestinal segment (i.e., speed highest in duodenum, lowest in ileum/colon). No serious adverse events were reported in the literature, and a dropout rate of around 10% was found for these types of studies. This review is highly relevant for researchers who are active in various research areas and want to expand their research with the use of intestinal catheters in humans in vivo.